KREDIBILITAS PEMBERITAAN MEDIA BATAM POS TERHADAP PERSEPSI COVID-19 MASYARAKAT KOTA BATAM - Juniati, Yosiana; Rorong, Michael Jibrael (LPPM Universitas Putera Batam, 2021)
The purpose of this study is to determine the influence of the credibility of the Batam Pos media covarage on the perception of Covid-19 of the Batam city. Media coverage over the past few years has been filled with news related to Covid-19 or the corona virus. This deadly virus is so interesting to discuss and has given a different perception among the public. The research method used is a quantitative method with the type of survey research. Based on the results obtained from data processing, there is an influence of Batam Pos media credibility on the perception of Covid-19 of the people of Batam city based on t-test analysis, this presents table t count > t table 7.073 > 0.155, which means there is a significant effect at a significant level of 10%. The influence of the credibility of the Batam Pos media on the perception of Covid-19 of the people of the city of Batam is evidenced by the results of the 33.8% analysis of the impact of Batam Pos media credibility.